Halal Certification from The Perspective of Maqashid Shariah: A Strategy to Enhance The Added Value of Msmes in Pekalongan District, East Lampung - Rizqi, Retanisa; Nabila, Cindy Firantika; Bahari, Raha; Widyastuti, Mila (Likuid Jurnal Ekonomi Industri Halal, 2025)
This study aims to examine the application of halal certification in Micro, Small, and Medium Enterprises (MSMEs) food products in Pekalongan District, East Lampung Regency, from the perspective of Maqosid Sharia. Halal certification is an important effort to ensure the halalness of products consumed by the Muslim community. This aligns with the government's policy to strengthen the guarantee of halal products in Indonesia. This study uses a descriptive qualitative approach with interview and documentation methods from 11 MSME actors. The study results show that several MSMEs in Pekalongan have obtained halal certification. Still, many have not met the requirements due to a lack of knowledge, administrative costs, and the complexity of the bureaucratic process. From the perspective of Maqosid Syariah, halal certification provides benefits in protecting the religion, soul, and property of consumers, as well as increasing the competitiveness of products in the market. It is hoped that there will be wider socialization and simplification of the administrative process to support MSME actors in obtaining halal certification.